2011
DOI: 10.7150/ijms.8.540
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of QT and P Wave Dispersion and Mean Platelet Volume among Inflammatory Bowel Disease Patients

Abstract: Background: In inflammatory bowel disease (IBD) number of thromboembolic events are increased due to hypercoagulupathy and platelet activation. Increases in mean platelet volume (MPV) can lead to platelet activation, this leads to thromboembolic events and can cause acute coronary syndromes. In IBD patients, QT-dispersion and P-wave dispersion are predictors of ventricular arrhythmias and atrial fibrilation; MPV is accepted as a risk factor for acute coronary syndromes, we aimed at evaluating the correlations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
36
2
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 42 publications
4
36
2
2
Order By: Relevance
“…Probable reasons for this inconsistency may include the following: only, patients with UC were included in our study, their study was not a prospective follow‐up study for AF development, and the number of active patients included in our study was too low. In a study by Yuksel et al evaluating ECG, P‐wave dispersion was shown to be increased in patients with IBD, and IBD was shown to be associated with AF . Although increased P‐wave dispersion values were detected in patients with UC in our study, the results were not statistically significant.…”
Section: Discussioncontrasting
confidence: 91%
See 1 more Smart Citation
“…Probable reasons for this inconsistency may include the following: only, patients with UC were included in our study, their study was not a prospective follow‐up study for AF development, and the number of active patients included in our study was too low. In a study by Yuksel et al evaluating ECG, P‐wave dispersion was shown to be increased in patients with IBD, and IBD was shown to be associated with AF . Although increased P‐wave dispersion values were detected in patients with UC in our study, the results were not statistically significant.…”
Section: Discussioncontrasting
confidence: 91%
“…In a study by Yuksel et al evaluating ECG, P-wave dispersion was shown to be increased in patients with IBD, and IBD was shown to be associated with AF. 24 Although increased P-wave dispersion values were detected in patients with UC in our study, the results were not statistically significant.…”
Section: Discussioncontrasting
confidence: 76%
“…There are relatively fewer studies on the relation between IBD and arrhythmias. One study that compared P‐wave dispersion on surface electrocardiography, which is considered as a risk factor for the development of AF, found that patients with IBD showed an increased P‐wave dispersion than controls . Another study showed AF prevalence found to be higher for all ages in IBD than in controls .…”
Section: Discussionmentioning
confidence: 99%
“…One study that compared P-wave dispersion on surface electrocardiography, which is considered as a risk factor for the development of AF, found that patients with IBD showed an increased P-wave dispersion than controls. 20 Another study showed AF prevalence found to be higher for all ages in IBD than in controls. 9 A recent nationwide cohort study consisting of 24 499 patients and 236 275 matched controls revealed that IBD was associated with twofold increased risk of AF during active disease stages independent of age, gender, and potential confounding factors and the risk of stroke was also elevated in patients with IBD during active stages like AF.…”
Section: For Comparisons Between Ibd Patients On Remission and Controlsmentioning
confidence: 96%
“…The literatures suggested that sympathetic activity changes could be the reason for QT and QTc interval alterations and increased QT dispersion and QTc dispersion of ventricular repolarisation [29, 30]. In contrast to these studies, Dogan et al did not find any significant difference in QTdisp values between 69 IBD patients and controls [27]. …”
Section: Discussionmentioning
confidence: 99%